Corporate social responsibility and tax avoidance - Laszlo Goerke (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2018)
We theoretically analyse the relationship between Corporate Social Responsibility (CSR) and tax avoidance of an oligopolistic firm. The firm maximises a weighted sum of profits and a CSR objective which depends on output and the firm's contribution to public good provision, i.e. tax payments. Making one CSR element more important induces the firm to adhere less to the other and to reduce tax avoidance. Hence, simultaneously a substitutive and a complementary relationship between CSR and tax avoidance can be observed. Therefore, employing composite indicators of CSR prevents an empirical identification of this linkage. Moreover, if tax avoidance declines, CSR activities will increase. Consequently, the overall link between CSR and tax avoidance is theoretically ambiguous.
Keywords: H26; L13; L31; M14; 330; Corporate Social Responsibility; Public Good; Oligopoly; Output; Tax Avoidance